Arquitectura blockchain híbrida para el registro de historiales médicos - Son Romero, Alejandro Hernán (2025)
This article introduces a hybrid blockchain architecture to enhance Electronic Medical Record (EMR) management and interoperability. It integrates a permissioned public blockchain on Polkadot—managing roles and permissions—with a private blockchain on Hyperledger Fabric responsible for EMR storage. Text data are stored in CouchDB and medical images in IPFS as Non-Fungible Tokens (NFTs), following a patient-centric model. Stress tests yielded average latencies of 2050 ms for EMR creation and 2000 ms for sharing, with 65 % CPU and 170 MB memory usage, indicating system stability and efficiency. The proposed architecture provides a scalable, secure, and interoperable solution suitable for healthcare environments that demand data confidentiality and controlled access.